Caracterización geológica – geotécnica de la vía de acceso al Parque Nacional Podocarpus, desde Cajanuma hasta el Refugio Nº1, ubicado en el cantón y provincia de Loja. - Jara Torres, Michelle Anahi (2022)
The present investigation work "Geological-geotechnical characterization of the access road to the Podocarpus National Park, from Cajanuma to Refuge Nº1, located in the Canton and Province of Loja" focused on identifying and determining the geological and geotechnical characteristics through the application of direct and indirect methods which indicate soil resistance, moisture content, etc. It began with a detailed topographic survey of the study area, which covers a total of 80 ha. The topography of the study area is quite rugged, with reliefs that vary from 2600-3000 m.a.s.l. in the highest part, to heights of 2300 m.a.s.l. in the lowest part. The geology was obtained from the description of outcrops, where it was determined that the area is mostly made up of phyllites, shales and schists of the Chigüinda Unit and materials of the Quillollaco Formation (conglomerates). The geotechnical data were obtained by the direct method: 8 test pits were made to obtain in situ and laboratory data. In addition, three seismic lines were obtained in order to corroborate the geology with that observed on surface and to obtain physical properties of the materials. This study is aimed at proposing recommendations for the rectification and improvement of the Cajanuma road to the First Refuge of the Podocarpus National Park, after sampling, development of tests and field parameter surveys. Likewise, in the case of the rock massifs, the geomechanical classification RQD, RMR, GSI and SMR was carried out to determine slope stability. Keywords: Seismic Refraction, Standard Penetration Test, CBR, PROCTOR, geomechanical classification.